OGC P02 A comparison of body composition changes between the FLOT and MAGIC regimes in patients with locally advanced oesophageal cancer. (7th December 2022) - Liew, Mei Sien; Almonib, Ahmed; Al-Najjar, Yousif; Siddaiah-Subramanya, Manjunath; Tan, Benjamin
Abstract: Background: Recently, peri-operative FLOT (fluorouracil plus leucovorin, oxaliplatin, and docetaxel) chemotherapy has superseded the 'MAGIC' regimen (epirubicin, cisplatin plus fluorouracil or capecitabine) as standard of care for locally advanced oesophago-gastric adenocarcinoma. However, concerns have been raised regarding the toxicity profile of FLOT. This study aims to compare the changes in body composition between both regimens. Methods: 115 patients treated with FLOT (n = 61) or MAGIC (n = 54) who underwent an oesophagectomy for oesophageal or gastro-oesophageal junction (GOJ) adenocarcinoma between 2014 and 2020 at Queen Elizabeth Hospital, Birmingham, UK were analysed. Changes in body composition between pre- and post-neo-adjuvant chemotherapy were determined by analysis of computed tomography imaging. Results: In both regimes, a large proportion of patients were sarcopenic prior to starting chemotherapy (FLOT 44.2%, MAGIC 44.4%; p=0.984). The percentage of patients who were sarcopenic increased post chemotherapy (FLOT 63.9%, MAGIC 57.4%; p=0.474). There was no significant pre vs post chemotherapy change in L3 skeletal muscle index in both regimes (FLOT 2.96 ± 4.03 vs MAGIC 2.76 ± 4.21; p=0.792). There was also no significant pre vs post chemotherapy change in L3 fat index in both regimes (FLOT 2.49 ± 22.6 vs MAGIC 5.78 ± 24.2; p = 0.453). Myosteatosis was observed in 44.3% of patients pre-FLOT and 42.6% of patients pre-MAGIC (p=0.857). This increased to 62.2% post-FLOT and 46.3% post-MAGIC (p=0.085). FLOT chemotherapy was associated with better tumour regression grade compared to MAGIC (p<0.001). Conclusions: A large proportion of patients with locally advanced oesophageal/GOJ adenocarcinoma were sarcopenic and had myosteatosis prior to starting chemotherapy. A further loss of muscle and fat occurs during chemotherapy but there was no significant difference in loss of fat or muscle across both FLOT and MAGIC regimes. However, patients treated with the FLOT regime had better pathological response as compared with MAGIC.